2015
DOI: 10.4172/2375-4427.1000127
|View full text |Cite
|
Sign up to set email alerts
|

An Acoustical Analysis of the Frequency-Attenuation Response of Musician Earplugs

Abstract: Musician earplugs (MEP) are intended to reduce the risk for noise induced hearing loss among musician populations while providing flat attenuation characteristics. However, survey data suggest that low use rates among musicians are associated with negative listening experiences due to perceived alterations in the spectral characteristics of music. These shortcomings warrant the assessment of how a MEP processes the full frequency and complex spectral nuances of musical sounds. The goal of this study was to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Earplug wearers have not necessarily worn the products correctly, and results of real-world noise circumstances versus laboratory testing often greatly overestimated attenuation of the earplug products. Musicians' earplugs, in particular, have a history of problems with accurate fit, occlusion effect (sound conducted through the bones of the ear that reverberates inside the head), and poor attenuation (Chesky & Amlani, 2015;Chesky et al, 2009;O'Brien, Ackerman, et al, 2014;O'Brien, Driscoll, et al, 2014). In fact, a recent report indicated discrepancies among marketed versus actual attenuation levels of custom and noncustom earplugs, as well as the measured differences in spectral characteristics of music when using various earplugs (Chesky & Amlani, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earplug wearers have not necessarily worn the products correctly, and results of real-world noise circumstances versus laboratory testing often greatly overestimated attenuation of the earplug products. Musicians' earplugs, in particular, have a history of problems with accurate fit, occlusion effect (sound conducted through the bones of the ear that reverberates inside the head), and poor attenuation (Chesky & Amlani, 2015;Chesky et al, 2009;O'Brien, Ackerman, et al, 2014;O'Brien, Driscoll, et al, 2014). In fact, a recent report indicated discrepancies among marketed versus actual attenuation levels of custom and noncustom earplugs, as well as the measured differences in spectral characteristics of music when using various earplugs (Chesky & Amlani, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Since earplugs were developed for industry-specific applications and not for music environments (until more recently), new data suggest that “the spectral characteristics of music are altered by MEPs [musicians’ earplugs], regardless of whether the earplug was non-custom or custom” (Chesky & Amlani, 2015, p. 4). In the same article by Chesky and Amlani (2015), there also seemed to be disparity among the stated attenuation characteristics of custom and noncustom earplugs popularly marketed toward musicians. The researchers reported that custom-made earplugs with the 9-dB and 15-dB filters had higher attenuation rates than published (12.5-dB and 16-dB, respectively).…”
mentioning
confidence: 99%
“…Musicians' dissatisfaction with the impact of HPDs on music listening and playing also highlights fundamental flaws with the design, specification and fitting of high-fidelity musicians' earplugs, which need addressing (O 0 Brien, Ackermann, and Driscoll 2014;Zander, Spahn, and Richter 2008). Indeed, the detrimental impact of HPDs on music listening and performance is not necessarily subjective, given that it has been shown that highfidelity musicians' earplugs can lead to an occlusion effect (Bernier and Voix 2013;Killion 2012), sound localisation difficulties (Chasin and Chong 1999), and altered spectral characteristics (Chesky and Amlani 2015); they have also been shown to alter the sound level and spectrum of played sounds (Kozłowski, Zera, and Mły nski 2011) and result in less resonant choral singing (Cook-Cunningham 2019).…”
Section: Environmental Restructuringmentioning
confidence: 99%
“…Less than 10% of the musicians reported using such protection frequently. A literature review suggests that musician reports very limited use of HPDs due to pain; pressure; discomfort; HPDs' inference with playing and monitoring ability; and distortion of timbre, dynamics, and sonority when they and their peers are playing [13,[29][30][31][32][33]. To cater to the hearing protection needs of the musicians, HPD manufacturers developed musicians' ear plugs (MEPs), claiming that MEPs replicate the natural response of the ear canal and offer adequate attenuation without compromising the spectrum of music and listening quality [33].…”
Section: Marching Band Members' Perceptions Of Hearing Health Riskmentioning
confidence: 99%
“…To cater to the hearing protection needs of the musicians, HPD manufacturers developed musicians' ear plugs (MEPs), claiming that MEPs replicate the natural response of the ear canal and offer adequate attenuation without compromising the spectrum of music and listening quality [33]. However, Chesky and Amlani [32] found that the claims used to market MEPs to musicians are misleading. They reported discrepancies for claiming attenuation characteristics in response to musical sounds and attributed these, in part, to the manufacturers' testing procedures for measuring attenuation and listening quality [32].…”
Section: Marching Band Members' Perceptions Of Hearing Health Riskmentioning
confidence: 99%